STABILITY IN TWO-STAGE STOCHASTIC INTEGER PROGRAMMING - Esther Nababan (Proceedings of ICMSA, 2005)
There is a large number of different approaches for formulating andsolving optimization problems under uncertainty. In applications, one isusually faces incomplete information on probability measure u.Numerical attemps has been made mostly rely on approximating u by